IMPLEMENTASI KEBIJAKAN PENERBITAN SURAT IJIN MENGEMUDI DI POLRES PALU TERHADAP PELANGGARAN DAN KECELAKAAN LALU LINTAS DI KOTA PALU - manajerpasca, manajerpasca (Vol 1, No 2 (2012), 2012)
This research aimed at analyzing the policy implementation of a driver's license (SIM) issuance at Polres Palu towards traffic violations and accidents in Palu; and to find out factors that influenced those violations, accidents and inappropriateness of a driver's license issuance. All 114 policemen in Palu Police Resort became the population of this research and 30 of them were selected as sample. The data were collected through observation, interview, questionnaire and documentation. The result showed that the policy implementation of a driver's license issuance at Polres Palu which consisted of four indicators: communication, resources, impact and bureaucracy were carried out properly. The occurrence of traffic accidents and violations due to the acquisition of SIM which was inappropriate with the rule and less understood of drivers about traffic rules. Factors affected traffic violations, accidents and public driving license issuance, were the low level of public confidence to the police, bureaucracy effect in solving the cases remained high, resolving the case of violations committed by members of PolriÂ were not transparent and tend to be protected by corps, and level of welfare and incentives was inadequate and unsupported by budget and adequate infrastructure. All of those factors were considered as the effects of Polres Palu apparatus performance to be less maximum in improving legal services in their area. Key words: Policy, implementation and traffic accidents